Intimate Partner Violence in Pregnancy: Knowledge and Experiences of Pregnant Women and Controlling Behavior of Male Partners in Sokoto, Northwest Nigeria - Oche, Oche Mansur; Adamu, Habibullah; Abubakar, Aisha; Aliyu, Munira Sahabi; Dogondaji, Abubakar Shehu (International Journal of Reproductive Medicine, 2020)
Background. Violence against women perpetrated by an intimate partner is an important public health issue. In recent years, attention has focused also on intimate partner violence (IPV) during pregnancy due to its prevalence, adverse health consequences, and intervention potentials. Aim. To determine the knowledge, experiences, and factors influencing IPV, including the controlling behaviors of male partners of pregnant women attending an antenatal clinic (ANC) of a tertiary health facility in Sokoto. Materials and method. A descriptive cross-sectional study was conducted among 260 pregnant women attending ANC in a tertiary health facility in the Sokoto metropolis. They were selected using a systematic sampling technique, and a set of pretested questionnaire items was used for data collection. Data were analysed using IBM SPSS version 20. Results. The respondents’ ages ranged from 19 to 40 years with a mean of 29.09±4.99 years, and up to 83.5% of them were in a monogamous setting. Three-quarters of them were Muslims mostly from urban areas (72.1%), and 36.4% had a university or HND degree. Majority of them responded correctly to questions on IPV; overall, up to 99.2% of them had good knowledge of IPV. About 33% of the respondents have experienced IPV while pregnant and up to 61.7% of them said they did nothing because of fear. Some of the controlling behaviors of male partners included always asking for permission before seeing friends and family members and also controlling their finances. Factors associated with IPV include tribe, place of residence, and partner consuming alcohol. Conclusion. Majority of the respondents had good knowledge of IPV with about one-third of them ever experiencing it. Respondent’s partners were mostly jealous and exhibited some form of controlling behaviors. Physical violence was the most prevalent form, and most of the victims did nothing about it. Government and women’s right groups should push for the implementation of tougher punitive measures against perpetrators of IPV.